Epitranscriptomics of Mammalian Mitochondrial Ribosomal RNA - Laptev, Ivan (Cells, 2020)
Modified nucleotides are present in all ribosomal RNA molecules. Mitochondrial ribosomes are unique to have a set of methylated residues that includes universally conserved ones, those that could be found either in bacterial or in archaeal/eukaryotic cytosolic ribosomes and those that are present exclusively in mitochondria. A single pseudouridine within the mt-rRNA is located in the peptidyltransferase center at a position similar to that in bacteria. After recent completion of the list of enzymes responsible for the modification of mammalian mitochondrial rRNA it became possible to summarize an evolutionary history, functional role of mt-rRNA modification enzymes and an interplay of the mt-rRNA modification and mitoribosome assembly process, which is a goal of this review.